MHC variation, multiple simultaneous infections and physiological condition in the subterranean rodent Ctenomys talarum - Cutrera, Ana Paula (2011)
Parasites and pathogens can play a signiﬁcant role in shaping the genetic diversity of host populations, particularly at genes associated with host immune response. To explore this relationship in a natural population of vertebrates, we characterized Major Histocompatibility Complex (MHC) variation in the subterranean rodent Ctenomys talarum (the talas tuco-tuco) as a function of parasite load and ability to mount an adaptive immune response against a novel antigen. Speciﬁcally, we quantiﬁed genotypic diversity at the MHC class II DRB locus in relation to (1) natural variation in infection by multiple genera of parasites (potential agents of selection on MHC genes) and (2) antibody production in response to injection with sheep red blood cells (a measure of immunocompetence). Data were analyzed using coinertia multivariate statistics, with epidemiological proxies for individual condition (hematocrit, leukocyte proﬁle, body weight) and risk of parasite exposure (season of capture, sex). A signiﬁcant excess of DRB heterozygotes was evident in the study population. Co-inertia analyses revealed signiﬁcant associations between speciﬁc DRB alleles and both parasite load and intensity of humoral immune response against sheep red blood cells. The presence of speciﬁc DRB aminoacid sequences appeared to be more strongly associated with parasite load and response to a novel antigen than was heterozygosity at the DRB locus. These data suggest a role for parasite-driven balancing selection in maintaining MHC variation in natural populations of C. talarum. At the same time, these ﬁndings underscore the importance of using diverse parameters to study interactions among physiological conditions, immunocompetence, and MHC diversity in free-living animals that are confronted with multiple simultaneous immune challenges